PSYCHOSOCIAL FACTORS AND ASSOCIATED SYMPTOMS IN PATIENTS WITH FUNCTIONAL NEUROLOGICAL SYMPTOM DISORDER - Rasheed, Farah; Adeena Rasheed; Rizwan Mushtaq Bhutta; iqbal, Khizra (Journal of Pakistan Psychiatric Society, 2025)
OBJECTIVE To investigate the symptom type, sociodemographic factors and preceding events in patients with Functional Neurological Symptom Disorder (FNSD). STUDY DESIGN Cross-sectional study PLACE AND DURATION OF STUDY The study was conducted at Nishtar Medical University Hospital, Multan, Pakistan, from 1st January 2024 to 1st March 2024 (a three month period). METHOD Data were collected through a purposive sampling technique from 50 patients diagnosed with FNSD. The Conversion Disorder Questionnaire (Australian Paediatric Surveillance Unit) was used to assess symptom types, and a structured proforma gathered demographic information and psychosocial stressors. RESULTS Symptoms of FNSD occurred more frequently among females, unmarried individuals, those with lower education, low socioeconomic status, living in joint families, and belonging to rural areas. Most patients presented with acute symptoms. CONCLUSION Female gender, lower level of education, economic disadvantage, joint family structure, rural residence and single marital status appear to be the sociodemographic factors most commonly associated with FNSD in this study sample. Recognising these factors may support earlier detection and improved intervention.